Insights into Structural Transformations of Lignin Toward High Reactivity During Choline Chloride/Formic Acid Deep Eutectic Solvents Pretreatment - Hong, Si; Shen, Xiao-Jun; Sun, Zhuohua; Yuan, Tong-Qi (Frontiers in Energy Research, 2020)
Understanding lignin structural transformations during DES pretreatment would facilitate to produce lignin with tailor-made properties based on intended applications. To unravel the structural variant of lignin in the DES, the alkali lignin (AL) was pretreated in choline chloride/formic acid (ChCl/FA) (the ratio of 1:2) at 80-120 oC. Characterization of the AL and regenerated lignin samples were determined to understand lignin structure, such as linkage in lignin, phenolic OH content, molecular weight, and aromatic products. ChCl/FA DES pretreatment resulted in large amounts of the dissociation of β-O-4' bonds, partial cleavage of carbon-carbon bonds (i.e., β-β′, β-5′), dehydration of hydroxyl radicals in lignin’s side-chain, and demethoxylation reaction. Furthermore, various monomeric phenols derived from AL were also determined in spite of low combined yields, which facilitate the production of fine chemicals in the future. Detailed unmasking of lignin structural transformation during the DES process is conducive to the optimizing preparation of homogeneous lignin with low molecular weight.